A Portrait of Intimate Apparel Female Shoppers: A Segmentation Study. Issue 1 (February 2017) - Tsarenko, Yelena; Lo, Carolyn J.
This research expands dialogue on the dynamic consumer–product relationship within the under-researched, albeit sensitive, context of intimate wear. Drawing on involvement theory alongside specific product and service attributes, this study delineates and profiles segments within the highly engendered consumption of the bra. Data gathered from 221 Australian females unveiled three distinct segments of female bra shoppers: Enthusiasts who derive significant hedonic value in purchasing bras, Dilettantes who portray high interest in lingerie but exhibit the lowest levels of competency in bra-shopping, and Pragmatists who hold the lowest score in terms of hedonic value but perceive themselves as highly competent bra shoppers. Demographic and attribute profiling further captures differences between segments on factors including age, brand importance, lingerie servicescape ambience, and professional fitting advice. Findings provide relevant insights for lingerie retailers and suggestions for future research.